The Effect Of Recreational Sports Activities On Learning Interest In Third Grade Students At SD Negeri 2 Cinagara - Kinanti Pratnya Nalendra; Dani Nurdiansyah (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to determine the effect of recreational sports activities on the learning interest of third-grade students at SD Negeri 2 Cinagara. The background of this research is the low learning interest of students, influenced by monotonous teaching methods and a lack of teacher innovation. Recreational sports were chosen as a learning strategy that combines elements of games, fitness, and fun. The method used was a quantitative approach with a pre-experimental one-group pretest–posttest design. The research sample consisted of 38 students. Data were collected through observation, questionnaires, and documentation, along with instrument validity testing. Descriptive analysis results showed that the average pretest score was 40.58 and the posttest score was 86.00, with the lowest score increasing from 26 to 66 and the highest score from 54 to 100. Normality testing using the Shapiro–Wilk method indicated normally distributed data. Hypothesis testing using the Paired Sample T-Test yielded a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. Therefore, H₀ was rejected and Hₐ accepted, concluding that recreational sports activities positively affect students’ learning interest.